The System Effect: Scaling High‐Impact Practices Across Campuses. Issue 169 (March 2015) - Gagliardi, Jonathan S.; Martin, Rebecca R.; Wise, Kathleen; Blaich, Charles
Abstract : This chapter examines the role of systems and consortia in scaling and implementing undergraduate research through a study of the efforts of six systems and consortia working together with the Council on Undergraduate Research.